Listening Team And Team Quiz Learning Model Implementation Towards Student’s Study Results On Social Science Subject In Islamic Junior High School - Bashith, Abdul; Nasith, Ali (International Journal of Educational Research & Social Sciences, 2022)
This article is about improving learning through listening teams and quizzes. Seeing the phenomenon of the low level of completeness of students in understanding the material presented in class, because they still use the lecture method which is considered less than optimal. So that the concept of the material is not understood by students. Therefore, we need a solution in teaching and learning activities to overcome the problems above, namely by using the Listening Team and Team Quiz methods as an alternative offer because it can arouse students’ enthusiasm and enthusiasm and develop children’s potential optimally. Experiments of listening team and team quiz learning models on student study results in Islamic Junior High School (Madrasah Tsanawiyah), especially in Social Sciences subjects (IPS).